Adam Smith's marketplace of life - Otteson, James R. (Cambridge University Press, 2002)
James Otteson provides a comprehensive examination of Smith's moral theory. Considering Smith's notions of natural sympathy, the impartial spectator, human nature, and human conscience the author also addresses the issue of whether Smith thinks that moral judgments enjoy a transcendent sanction.